Long-term Effects of Statins, Blood Pressure-Lowering, and Both on Erectile Function in Persons at Intermediate Risk for Cardiovascular Disease : A Substudy of the Heart Outcomes Prevention Evaluation-3 (HOPE-3) Randomized Controlled Trial (2018)
7 p.